Qualitative protocol to support detection of the early presentation and diagnosis of mycetoma in Sudan - Ackley, Caroline; Hall, Victoria; Ahmed, Eiman S.; Hounsome, Natalia; Elsheikh, Mohamed N.; Zaman, Shahaduz; Bakhiet, Sahar (Frontiers in Tropical Diseases, 2024)
The neglected tropical disease (NTD) mycetoma is a chronic and progressively destructive infectious disease endemic in Sudan. There is a growing body of scientific research on mycetoma -causes, transmission, treatment, and impact from a clinical and biomedical perspective. However, there is further need for in-depth medical anthropology research on the disease to successfully translate biomedical advances into elimination and control programmes. Given this background the NIHR Global Health Research Unit on NTDs at Brighton and Sussex Medical School is leading multidisciplinary research on skin NTDs, including mycetoma, with a medical anthropology research component exploring how community engagement can lead to earlier presentation of mycetoma in Sudan. This protocol paper sets out the research aims and methods to generate new knowledge on mycetoma in Sudan once the political situation becomes stable and it is safe to carry out global health research once again. We continue to develop appropriate community engagement intervention strategies, while activities like training and capacity strengthening get underway remotely. In what follows we situate this study in the NIHR Research Unit on NTDs and alongside social science research on mycetoma. This study is part of the programme of research conducted by the NIHR Research Unit on NTDs at Brighton and Sussex Medical School (BSMS). Phase I of the Unit was conducted from 2018–2021. Below we detail key findings from Phase I that have informed our more recent work in Phase II (2021)(2022)(2023)(2024)(2025)(2026). It also sits alongside the Social Sciences for Severe Stigmatising Skin Conditions (5-S) Foundation also at BSMS (‘NIHR 5S Foundation -BSMS’ n.d., 5). The 5-S foundation examines the cultural, social, economic, and policy contexts of podoconiosis, mycetoma, and scabies in relation to the dynamics and dimensions of stigma. This study differs from the aims of the 5S Foundation in that it specifically focuses on the role community engagement can have in the early presentation and diagnosis of mycetoma in Sudan.